The effect of Pangium edule (kluwek) extract on the discoloration of resin composite microhybrids: an experimental laboratory - Ibrahim, Irsan; Alawiyah, Tuti; Amelia, Herlin (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: Composite resin is a restoration material that is often used because it has high aesthetic value. Hybrid composite resins are currently one of the most popular materials for aesthetic restoration. This is due to several advantages, including low shrinkage, low abrasion, and better surface smoothness than small-particle composite resins. Pangium edule is a spice used in a variety of dishes, including rawon, brongkos vegetables, and konro soup. Apart from its function as a flavouring, Pangium edule also makes food browner in color. This Kluwekstudy aims to analyze the effect of Pangium edule extract on the discoloration of resin composite microhybrids. Methods: Type of research is experimental laboratory use of 24 microfiller hybrid resin composite specimens with a diameter of 6 mm and a thickness of 2 mm were used. The 24 specimens were divided into three groups based on their soaking time: 1 day, 3 days and 5 days, to see any color changes. Each treatment time group consisted of 8 specimens soaked in the Pangium edule solution. The Vita Easy Shade tool was used to verify color change measurements. Analyzed data using the one-way Anova test Results: The one-way Anova test findings revealed a significant difference (p=0.000) in the color change of composite resin that was soaked in Pangium edule solution for one, three, and five days. Conclusion: The change in the color of microhybrid composite resin soaked in Pangium edule solution for 1 day, 3 days and 5 days can cause color changes, especially in the hue value.KEYWORDSdiscoloration, resin composite microhybrid, Pangium edule